Major royal-jelly proteins intake modulates immune functions and gut microbiota in mice - Hang Wu; Shican Zhou; Wenjuan Ning; Xiao Wu; Xiaoxiao Xu; Zejin Liu; Wenhua Liu; Kun Liu; Lirong Shen; Junpeng Wang (Food Science and Human Wellness)
In this study, we investigated the effects of major royal jelly proteins (MRJPs) on the estrogen, gut microbiota, and immunological responses in mice. Mice given 250 or 500 mg/kg, not 125 mg/kg of MRJPs, enhanced the proliferation of splenocytes in response to mitogens. The splenocytes and mesenteric lymphocytes activated by T-cell mitogens (ConA and anti-CD3/CD28 antibodies) released high levels of IL-2 but low levels of IFN-γ and IL-17A. The release of IL-4 was unaffected by MRJPs. Additionally, splenocytes and mesenteric lymphocytes activated by LPS were prevented by MRJPs at the same dose as that required for producing IL-1β and IL-6, two pro-inflammatory cytokines. The production of IL-1β, IL-6, and IFN-γ was negatively associated with estrogen levels, which were higher in the MRJP-treated animals than in the control group. Analysis of the gut microbiota revealed that feeding mice 250 mg/kg of MRJPs maintained the stability of the natural intestinal microflora of mice. Additionally, the LEfSe analysis identified biomarkers in the MRJP-treated mice, including Prevotella, Bacillales, Enterobacteriales, Gammaproteobacteria, Candidatus_Arthromitus, and Shigella. Our results showed that MRJPs are important components of royal jelly that modulate host immunity and hormone levels and help maintain gut microbiota stability.